Single Intramammary Infusion of Recombinant Bovine Interleukin-8 at Dry-Off Induces the Prolonged Secretion of Leukocyte Elastase, Inflammatory Lactoferrin-Derived Peptides, and Interleukin-8 in Dairy Cows - Atsushi Watanabe; Jiro Hirota; Shinya Shimizu; Shigeki Inumaru; Kazuhiro Kimura (Veterinary Medicine International)
A single intramammary infusion of recombinant bovine interleukin-8 (IL-8) at 50 μg/quarter/head, but not 10 μg/quarter/head, induced clinical mastitis in three of four cows during the dry-off period, resulting in an elevated rectal temperature, redness and swelling of the mammary gland, extensive polymorphonuclear leukocyte (PMNL) infiltration, and milk clot formation from 1 to 28 days post infusion (PI). In the mammary secretions of the mastitic glands, high levels of IL-8 were sustained from 8 hours to 28 days PI, peaking at 1–3 days PI. The levels of leukocyte-derived elastase and inflammatory 22 and 23 kDa lactoferrin derived peptides (LDP) were also increased in the mammary secretions from the mastitic glands. In addition to the experimentally induced mastitis, the mammary secretions from the glands of cattle with spontaneous Staphylococcus aureus dry-period mastitis displayed milk clot formations and significant increases in their levels of PMNL counts, elastase, LDP, and IL-8, compared with those of the mammary secretions from the uninfected glands. These results suggest that after an intramammary infusion of IL-8 has elicited inflammatory responses, it induces the prolonged secretion of elastase, inflammatory LDP, and IL-8, and that long-lasting IL-8-induced inflammatory reactions are involved in the pathogenesis of S. aureus dry-period mastitis.